Igniting the Influence of Debt to Equity Ratio and Return on Assets on Company Value In Banking Companies - Purnomo, Hadi; Prabantarikso, Mahelan (Borong Newinera Publisher, 2026)
This study aims to identify and empirically examine the effect of the Debt to Equity Ratio (DER) and Return on Assets (ROA) on firm value in Islamic Commercial Banks. The research adopts a quantitative approach using secondary data obtained from the financial statements of Islamic Commercial Banks consistently published during the 2020–2024 period on the official website of the Indonesia Stock Exchange. The population consists of 12 Islamic Commercial Banks listed on the exchange, from which 8 banks were selected as samples using a purposive sampling technique. The independent variables in this study are the Debt to Equity Ratio and Return on Assets, while firm value serves as the dependent variable. Data were collected through observation and documentation, then analyzed using SPSS version 26. The analytical techniques applied include validity and reliability tests, classical assumption testing, the coefficient of determination, and multiple linear regression analysis. The results indicate that both the Debt to Equity Ratio and Return on Assets have a partial effect on firm value. Furthermore, the simultaneous test results show that DER and ROA jointly have a significant effect on the firm value of Islamic Commercial Banks. The findings of this study are expected to contribute to the development of Islamic financial studies and provide empirical insights into the factors influencing firm value in Islamic banking, as well as serve as a reference for future research by incorporating additional relevant variables.